Tonotopic and localized pathways from primary auditory cortex to the central nucleus of the inferior colliculus - Markovitz, Craig D.; Tang, Tien T.; Lim, Hubert H. (Frontiers in Neural Circuits, 2013)
Descending projections from the cortex to subcortical structures are critical for auditory plasticity, including the ability for central neurons to adjust their frequency tuning to relevant and meaningful stimuli. We show that focal electrical stimulation of primary auditory cortex in guinea pigs produces excitatory responses in the central nucleus of the inferior colliculus (CNIC) with two tonotopic patterns: a narrow tuned (NT) pattern that is consistent with previous findings showing direct frequency-aligned projections; and a broad tuned (BT) pattern in which the auditory cortex can influence multiple frequency regions. Moreover, excitatory responses could be elicited in the caudomedial portion along the isofrequency laminae of the CNIC but not in the rostrolateral portion. This descending organization may underlie or contribute to the ability of the auditory cortex to induce changes in frequency tuning of subcortical neurons as shown extensively in previous studies.